PET Imaging of Synaptic Density: Challenges and Opportunities of Synaptic Vesicle Glycoprotein 2A PET in Small Animal Imaging - Toyonaga, Takuya; Fesharaki-Zadeh, Arman; Strittmatter, Stephen M.; Carson, Richard E.; Cai, Zhengxin (Frontiers in Neuroscience, 2022)
The development of novel PET imaging agents for synaptic vesicle glycoprotein 2A (SV2A) allowed for the in vivo detection of synaptic density changes, which are correlated with the progression and severity of a variety of neuropsychiatric diseases. While multiple ongoing clinical investigations using SV2A PET are expanding its applications rapidly, preclinical SV2A PET imaging in animal models is an integral component of the translation research and provides supporting and complementary information. Herein, we overview preclinical SV2A PET studies in animal models of neurodegenerative disorders and discuss the opportunities and practical challenges in small animal SV2A PET imaging. At the Yale PET Center, we have conducted SV2A PET imaging studies in animal models of multiple diseases and longitudinal SV2A PET allowed us to evaluate synaptic density dynamics in the brains of disease animal models and to assess pharmacological effects of novel interventions. In this article, we discussed key considerations when designing preclinical SV2A PET imaging studies and strategies for data analysis. Specifically, we compared the brain imaging characteristics of available SV2A tracers, i.e., [11C]UCB-J, [18F]SynVesT-1, [18F]SynVesT-2, and [18F]SDM-16, in rodent brains. We also discussed the limited spatial resolution of PET scanners for small brains and challenges of kinetic modeling. We then compared different injection routes, and estimated the maximum throughput (i.e., number of animals) per radiotracer synthesis by taking into account the injectable volume for each injection method, injected mass, and radioactivity half-lives. In summary, this article provides a perspective for designing and analyzing SV2A PET imaging studies in small animals.